Legal Formulation of Post-Divorce Maintenance: Neglect of Women and Children From The Perspective of Criminal Law and Habermas' Theory of Social Integration - Fatimah; Rika Afrida Yanti; Radhali; Vivi Hayati; Nurasyiah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Neglect of child support after divorce is a form of rights violation with serious social and legal consequences. Although regulated by civil and religious law, the reality shows weak implementation and minimal sanctions for violators. This article aims to analyze this issue through a juridical-sociological approach by examining the perspective of criminal law and Jurgen Habermas's theory of social integration. The results of the study indicate that neglect of child support can fulfill the criminal elements of child neglect as stipulated in Law No. 35 of 2014 concerning Child Protection. Meanwhile, neglect of an ex-wife can be examined through the economic violence approach in the Domestic Violence Law. Within Habermas's theoretical framework, this weak legal implementation reflects the failure of the legal system to build social legitimacy and rational communication between legal subjects. Therefore, legal reconstruction is needed that integrates normative, criminal, and communicative approaches. Recommendations include reform of child support regulations, strengthening post-divorce mediation, community-based legal education, and digitizing reporting and monitoring systems. Thus, the law can function as a fair, transformative, and responsive instrument of protection for women and children after divorce.